Bäcklund transformation, residual symmetry and exact interaction solutions of an extended (2+1)-dimensional Korteweg–de Vries equation. (February 2022) - Wu, Huiling; Chen, Qiaoyun; Song, Junfeng
Abstract: Starting from the truncated Painlevé expansion, auto- and non-auto Bäcklund transformations are constructed for an extended (2+1)-dimensional Korteweg–de Vries equation. Then nonlocal residual symmetry is derived and localized to obtain the finite group transformation. By virtue of a simple connection between the truncated Painlevé expansion and the consistent tanh expansion (CTE) method, exact single soliton and resonant two-soliton solutions as well as interaction solutions between soliton and cnoidal wave are presented explicitly.